Investigation of optimal bipedal walking gaits subject to different energy-based objective functions - Römer, Ulrich; Fidlin, Alexander; Seemann, Wolfgang (Proceedings in applied mathematics and mechanics, 2015)
Optimal bipedal walking gaits subject to different energy‐based objective functions are investigated using a simple planar rigid body model of a bipedal robot with upper body, thighs and shanks. The robot's segments are connected by revolute joints actuated by electric motors. The actuators' torques are generated by a trajectory tracking controller to produce periodic walking gaits. A numerical optimization routine is used to find optimal reference trajectories for average speeds in the range of 0.3 – 2.3 m/s to investigate the influence of different objective functions. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)